2004
DOI: 10.1002/cpp.415
|View full text |Cite
|
Sign up to set email alerts
|

Anger and aggression in people with intellectual disabilities: treatment and follow‐up of consecutive referrals and a waiting list comparison

Abstract: Based on the work of Novaco, there have been several reports of case illustrations that develop anger management training for people with intellectual disabilities. Case reports have become increasingly sophisticated, with social validation of aggression and follow-ups of up to 10 years. There have also been three recent outcome studies attesting to the effectiveness of anger management treatment methods. The current report uses more recently developed methods and a larger number of subjects than previous repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 17 publications
2
56
0
1
Order By: Relevance
“…However, allocation procedures in Rose et al (2008) and Rose et al There are issues associated with the lack of blinding across studies, with only five studies reporting that they attempted to blind the researchers who were responsible for measuring treatment (Benson et al, 1986;Hassiotis et al, In Press;Lindsay et al, 2004;Matson & Senatore, 1981;Willner et al, 2013). Six studies also reported the use of independent raters where masked assessment could not be guaranteed.…”
Section: Methodological Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, allocation procedures in Rose et al (2008) and Rose et al There are issues associated with the lack of blinding across studies, with only five studies reporting that they attempted to blind the researchers who were responsible for measuring treatment (Benson et al, 1986;Hassiotis et al, In Press;Lindsay et al, 2004;Matson & Senatore, 1981;Willner et al, 2013). Six studies also reported the use of independent raters where masked assessment could not be guaranteed.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Fourteen studies conducted follow-up measurements within three to six months post treatment, whereas four studies did not collect any follow-up data. Lindsay et al (2004) conducted the longest intervention with approximately forty group sessions of anger treatment over nine months which included up to thirty months of follow-up data for some participants.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Another very large effect (Cohen's d = 2.8) was seen using a personal diary-based measure of anger. 40 The PACS-IPT may represent a more suitable self-rating measure than the PI, particularly for people whose intellectual limitations make it difficult to imagine hypothetical situations. Although the PACS-IPT needs further development, it clearly shows potential as an alternative, and perhaps superior, measure of the response to actual provocations that the individual service user encounters.…”
Section: Development Of Novel Instrumentsmentioning
confidence: 99%
“…On the implementation of other cognitive interventions, similar results were obtained for anger management (Ahmadi & Abedi, 2002, Shakibayi et al, 2004Ashoori et al, 2008;Akton, 2000;Kellner et al, 2002, Lindsay et al, 2004. Yekta Shokouhi et al (2008) also showed that anger management training on anger reduction and increased use of anger control strategies have a positive impact.…”
Section: Discussionmentioning
confidence: 70%